Compliance with Weekly Iron Folic Acid Supplementation and Anemia among Adolescent Girls in Public Schools of Pokhara Metropolitan City - Acharya, Rachana; Sharma, Sharada; Acharya, Anita (Journal of Nursing and Health Sciences Nepal, 2025)
Introduction: Iron deficiency anemia is a major nutritional problem among adolescent girls. It affects their overall growth and development. In Nepal, the Ministry of Health and Population initiated the Weekly Iron Folic Acid Supplementation program for adolescent girls to combat anemia among adolescent girls. This study aims to assess the compliance with the weekly iron and folic acid supplementation and anemia among adolescent girls in Public Schools of Pokhara Metropolitan City.Methods: A cross- sectional study was conducted in two public schools in Pokhara Metropolitan City among adolescent girls aged 10-19 years. A total 260 sample was recruited using multistage probability sampling. Data was collected administering validated pretested structured self-administered questionnaires and blood samples were taken for hemoglobin estimation. For data analysis descriptive and inferential statistics were applied using SPSS version 16 for statistics.Results: The finding of the study concluded that 36.2 percent had compliance with Iron folic acid supplementation and 63.6 percent of adolescent girls had anemia. There was statistically significant association between level of iron and folic acid supplementation compliance with experience of side effects and sources of information (p